Application of Nurse-Led Graded Diaphragmatic Functional Training in Mechanically Ventilated Patients in the Intensive Care Unit: A Randomized Controlled Study - Xufeng Wu; Jianjian Zhang; Yuqing Wang; Yang Yang; Xin Meng; Yuyan Wu; Aihong Pan (Evaluation & the Health Professions, 2026)
Prolonged mechanical ventilation can impair diaphragmatic function and hinder weaning. This study evaluated the effect of nurse-led graded diaphragmatic functional training in mechanically ventilated ICU patients. In this single-center randomized controlled trial, 120 adult patients receiving mechanical ventilation in the intensive care unit of a tertiary hospital in Hefei from February to December 2024 were randomly assigned to either the intervention group (n = 60) or the control group (n = 60). The control group received routine rehabilitation care and early mobilization, while the intervention group received nurse-led graded diaphragmatic training in addition to standard care. Ultrasound was used to evaluate end-inspiratory diaphragm thickness, end-expiratory diaphragm thickness, diaphragm thickening fraction, diaphragmatic excursion, incidence of ventilator-associated pneumonia (VAP), and successful weaning rates before and 7 days after intervention. A total of 54 patients in the intervention group and 56 in the control group completed the study. After 7 days of intervention, the intervention group had significantly higher end-inspiratory diaphragm thickness, end-expiratory diaphragm thickness, diaphragm thickening fraction, diaphragmatic excursion, and weaning success rate, and a significantly lower incidence of VAP compared to the control group ( p < 0.05). Nurse-led graded diaphragmatic functional training improves diaphragmatic function, enhances weaning success, reduces ventilator-associated pneumonia, and promotes recovery in mechanically ventilated ICU patients.